Putative Target Proteins Of The Ribosomal Protein, Rpel27 In Nasopharyngeal Carcinoma Cells - Sim, Edmund Ui-Hang; Yew, Keh Li (Malaysian Society for Biochemistry & Molecular Biology, 2019)
The pathogenesis of nasopharyngeal carcinoma (NPC) is multifactorial and multigenic. Despite the identification of several NPC-associated ribosomal proteins (RPs), the roles of these factors and their interacting partners in NPC tumourigenesis are poorly understood. To date, NPC- associated RP genes are either up or down-regulated in diseased/tumour situation compared to normal condition. The ribosomal protein eL27 (RPeL27) has been known to be over-expressed at both transcript and protein levels in NPC cell lines. This hypothesis was reinforced by our study herein. More importantly, using gene knockdown (RNA interference technique) followed by 2D gelelectrophoresis (2D GE) and in silico analysis; we revealed 15 proteins that are likely to interact with RPeL27 during situation of NPC tumourigenesis. These include COTL1, MAGOHB, UBE2N, NDPKA, TMED10, PSMB6, CA2, PGAM1, RPeL14, RPeS8, TPI1,PSMA2, RPeL19, GSTP1, and TPM1. Their association with RPeL27 could attribute to gene expression alteration, cell migration disruption and invasion, promotion of cancer cell survival, immune evasion, and genomic instability. Our findings provide new theoretical insights into the mechanism and involvement of RPeL27 in NPC pathogenesis. This is pertinent in understanding the molecular pathogenesis mediated by ribosomal proteins in the malignancy of the nasopharyngeal tissues.